Event Pendidikan: A Need Assessment - Lailatussaadah, Lailatussaadah; Hayati, Salma; Sabila, Hidayatis; Muchfazillah, Nafhiza; Mawaddah, Mawaddah (Yayasan Putroe Ceudah Aceh, 2024)
This study aims to analyze the needs of event implementation in educational institutions. Needs analysis is done through interviews and questionnaires. Interviews and questionnaires were conducted on students of one of the study programs of the Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry Banda Aceh. Interviews were conducted on 20 students then analyzed interactively and thematically. Furthermore, the questionnaire was distributed to 103 students and analyzed with descriptive statistics. The results of the study found that students need educational events based on the objective indicator and students gave a positive response of 3.75 or 93.75%, on the type of educational event indicator, students need the type of event with a positive response of 3.71 or 92.75%. Furthermore, students need educational events on the Hybrid strategy aspect (online and offline) of 3.39 or 84.75%, and finally on the aspect of event characteristics, students said they needed events that had characteristics of 3.62 or 90.5%. Thus, it can be concluded that students need events implemented in educational institutions, so educational institutions need to pay attention to these needs.